A FRENCH-AUSTRALIAN COMPARISON OF RESPONSIBILITIES FOR THE MONITORING OF SECURITY AND PRIVACY ISSUES RESULTING FROM THE INTRODUCTION OF NEW INFORMATION TECHNOLOGIES - Batten, Lynn M; Le Grand, Gwendal (The journal of contemporary issues in business and government, 2007)
Information technologies have altered the way individuals, businesses and societies live and operate. Along with these changes has come loss of privacy and threats to the security of confidential information. Much research in the social sciences has established marked inter-relationships between technology, society and culture. However, the roles of corporations and governments in ensuring maintenance of security and privacy for citizens are unclear. This study determines and compares the roles and responsibilities of stakeholders in both France and Australia in monitoring and responding to security and privacy issues resulting from the introduction of new information technologies. It is found that governments in these countries remain at arm's length from regulation while investing many resources in education of the public and of small business concerning these issues.